PENGARUH PERSEPSI TENTANG MODEL PEMBELAJARAN MIND MAPPING, KETERAMPILAN DASAR MENGAJAR DAN KEDISIPLINAN BELAJAR TERHADAP PRESTASI BELAJAR IPS TERPADU - Dwi Destriani; Andriani Rosita; Udik Yudiono (Jurnal Riset Pendidikan Ekonomi, 2017)
Mind mapping learning model is a cooperative learning model that utilizez the brain as a center to obtain information by students by way of mapping his thought on the information contained in the material being studied, in addition to mind mapping learning model basic teaching skills must be considered by educator, in addition there are factors of students that affect the learning achievement of student discipline. The purpose of this study to determine the effect of mind mapping learning model, basic skills of teaching and student learning discipline simultaneously to the achievement of intregated IPS learning. Research method using quantitative research, type of ex-post-facto research. Population in this study is the Seventh grade students of SMP Islam Ma’arif 02 Malang academic year 2016/2017. Total population of 351 students and sample used 53 with proportional random sampling technique. Data collection is done by questionnaire and documentation method. Test data analysis requirements using descriptive analysis test and multiple linear regression analysis. The result of the analysis is 27,3 % simultaneously influence to the change of learning achievement